2019
DOI: 10.3390/ijerph16020259
|View full text |Cite
|
Sign up to set email alerts
|

Religious Coping, Religiosity, Depression and Anxiety among Medical Students in a Multi-Religious Setting

Abstract: Medical students are vulnerable to depression and anxiety due to the nature of their academic life. This study aimed to determine the prevalence of depressive and anxiety symptoms among medical students and the association between religious coping, religiosity and socio-demographic factors with anxiety and depressive symptoms. A cross sectional design was used for this study. Scales used were the Malay version of the Duke Religious Index (DUREL-M), the Malay version of the Brief Religious Coping Scale (Brief R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
90
1
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 39 publications
(46 reference statements)
7
90
1
13
Order By: Relevance
“…Similar link was described by Vasegh S as being close to statistical significance (p= 0.058) in a research carried out on a group of 285 medical students from Iran [24]. Francis B et al indicated that negative religious coping was linked to occurrence of depressive symptoms among 622 Malaysian medial students [25]. Our research didn't find a link between number of years after middle school after which one had entered medical studies and noticing symptoms that might had suggested depression during the course of medical studies.…”
Section: Discussionsupporting
confidence: 75%
“…Similar link was described by Vasegh S as being close to statistical significance (p= 0.058) in a research carried out on a group of 285 medical students from Iran [24]. Francis B et al indicated that negative religious coping was linked to occurrence of depressive symptoms among 622 Malaysian medial students [25]. Our research didn't find a link between number of years after middle school after which one had entered medical studies and noticing symptoms that might had suggested depression during the course of medical studies.…”
Section: Discussionsupporting
confidence: 75%
“…Several studies have reported that being religious or engaging in religious activities could help individuals to cope with mental health issues. 29 Malaysia is a Muslim majority country, with over 90% of the Muslims reported to be practicing their basic beliefs in Islam. 30 Therefore, based on these evidences, since the majority of our study sample were Malays and Muslims, this could explain that the students are coping well with depression, due to strong religious practices, and therefore explains the nonsignificant association between depression and eating disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research on motivational and affective factors of learning in university contexts has also recognized the importance of the different types of coping strategies used by university students. Some examples have addressed the role of religious coping (Francis et al, 2018), the role of health habits as a coping strategy (Tada, 2017), how coping strategies related to well-being (Park and Adler, 2003;Bhullar et al, 2014;Freire et al, 2016), types of coping and their relationship to resilience, academic coping within a religious vs. secular context (GonzĂĄlez-Torres and Artuch, 2014). The associations between coping strategies, anxiety and engagement-burnout have also been established (de la Fuente et al, 2015a).…”
Section: Coping Strategies In the Learning Processmentioning
confidence: 99%